APLIKASI ELECTRONIC SHORT STORY DALAM PEMBELAJARAN TOEFL BAGI DOSEN UNIVERSITAS LANCANG KUNING PEKANBARU - Fauzi, Mohd.; Muzdalifah, Indah (Universitas Lancang Kuning, 2017)
The title of this writing is “The application of Electronic Short Story in TOEFL Learning for Lecturers of University of Lancang Kuning.” The purpose of the writing is to socialize the use of strategy of Electronic Short Story Application, to increase participants’ motivation. To apply the strategy, the method used is describing and practicing. The result shows that lecturers get better motivation and comprehension in learning English for TOEFL preparation using the strategy of Electronic Short Story.